The Effect of Deep Breath Relaxation and Acupressure Point Li4 is Exposed to the Intensity of Labor Pain Kala I at the Duren Sawit Health Center in Jakarta - Eva Nurlaela; Feva Tridiyawati (PT FORMOSA CENDEKIA GLOBAL, 2022)
Childbirth is the most awaited moment for every mother around the world, but on the one hand it is a stressful thing. According to a 2018 data report by Riskesdas, there is a risk of childbirth complications that always lurks in every mother who undergoes the delivery process in Indonesia, one of which is the old partus triggered by mothers who are unable to adapt to the labor pain felt. Efforts to reduce pain during childbirth are divided into 2 methods, namely non-pharmacological and pharmacological methods. One of the many nonpharmacological methods of reducing pain is acupressurics and deep breath relaxation. The purpose of this study is to identify the effectiveness of LI4 point acupressure and deep breath relaxation as an effort to reduce the intensity and scale of labor pain the active kala I phase in mothers who are facing the delivery process at the Duren Sawit Jakarta Health Center for the May 2022 period. In this study, the author used the Quasy Experimental quantitative method, with a personal pre and post test design approach. The population chosen in the study were maternal clients who were going through the delivery stage when the first phase was active. Sample selection by total sampling method and using purposive sampling technique. The paired t-test is a test used for data analysis. The result after the study was carried out was that it was found that the ρ-value was 0.000, which means that both techniques are effective against pain reduction efforts.